Mendelian randomization analysis suggests no associations of human herpes viruses with amyotrophic lateral sclerosis - Zheng, Qingcong; Wang, Du; Lin, Rongjie; Chen, Yuchao; Huang, Haoen; Xu, Zixing; Zheng, Chunfu; Xu, Weihong (Frontiers in Neuroscience, 2023)
The causal relationship between infections with human herpes viruses (HHVs) and amyotrophic lateral sclerosis (ALS) has been disputed. This study investigated the association between herpes simplex virus (HSV), varicella-zoster virus (VZV), Epstein-Barr virus (EBV), cytomegalovirus (CMV), HHV-6, and HHV-7 infections and ALS through a bidirectional Mendelian randomization (MR) method. The genome-wide association studies (GWAS) database were analyzed by inverse variance weighted (IVW), MR-Egger, weighted median, simple mode, and weighted mode methods. MR-Egger intercept test, MR-PRESSO test, Cochran's Q test, funnelWhether there is an association between human herpes viruses (HHVs) infection and amyotrophic lateral sclerosis (ALS) has been controversial, and even little is known about the cause-and-effect relationship.